Nanoimprinting for all-polymer electro-optic waveguide devices - Henrique Franciele; Maeder Andreas; Talts Ülle-Linda; Finco Giovanni; Pohl David; Kaufmann Fabian; Reig Escalé Marc; Elder Delwin; Dalton Larry; Grange Rachel (EPJ Web of Conferences, 2023)
We performed the design and fabrication of polymer waveguide circuits, aiming for applications as electro-optic devices. Uniform waveguides with over one centimeter of length were fabricated by soft nanoimprint lithography. These multimode waveguides present a height of 3 µm and low surface roughness (2 nm), with a thin residual layer of 600 nm. Propagation losses at 1550 nm are estimated to be around 7 dB/cm.